Training on How to Prepare Two Main Course Recipes Using Lobi-Lobi and Gowok Fruits at Vocational High School (SMK) Gema Gawita – Tangerang - William Matthew; Valentino Jovan Emanuel; Sandra Maleach; Elang Kusumo (Jurnal Indonesia Sosial Sains, 2026)
The utilization of local Indonesian fruits as innovative culinary ingredients remains limited, despite their potential nutritional value, cultural significance, and economic opportunities. Fruits such as gowok (Syzygium polycephalum) and lobi-lobi (Flacourtia inermis) are still rarely incorporated into modern culinary products, particularly among vocational culinary students who require creativity and innovation skills to compete in the food industry. This community service activity aimed to improve students’ knowledge and skills in processing local fruits into innovative main course recipes while increasing awareness of the potential of local food resources. The activity was conducted using a participatory workshop method involving observation, educational sessions, cooking demonstrations, hands-on practice, and evaluation through pre-tests, post-tests, and participant satisfaction questionnaires. The results showed a significant improvement in students’ understanding of local fruit utilization and culinary innovation. The total correct answers increased from 102 in the pre-test to 137 in the post-test, with the average score improving from 3.64 to 4.89 and a knowledge increase of 34.3%. Furthermore, participants provided a very positive response, with an overall satisfaction score of 4.59, indicating that the training was effective and beneficial. In conclusion, this program successfully enhanced students’ culinary creativity, knowledge, and skills in utilizing local fruits as valuable ingredients for innovative culinary products.